2019
DOI: 10.1002/da.22899
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol awakening response and additive serotonergic genetic risk interactively predict depression in two samples: The 2019 Donald F. Klein Early Career Investigator Award Paper

Abstract: Background: The serotonin system and hypothalamic pituitary-adrenal (HPA)-axis are each implicated in the pathway to depression; human and animal research support these systems' cross-talk. Our work implicates a 5-variant additive serotoninergic multilocus genetic profile score (MGPS) and separately the cortisol awakening response (CAR) in the prospective prediction of depression; other work has shown that the serotonin transporter polymorphism 5HTTLPR predicts CAR and interacts with the CAR to predict depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Second, because the findings did not appear to fully depend upon any one of the four SNPs-all contributed effects in the same direction and overlapped in their effect size confidence intervals in both samples-this work supports the future use of additive models, especially those located within a single neurobiological system that can then inform specific etiological pathways. Third, the findings support further investigation of HTR2A and its variant rs6314, because this interacted at a trend level with the cortisol awakening response to predict depression in recent work (Vrshek-Schallhorn et al, 2019b) and significantly predicted cortisol reactivity in these findings.…”
Section: Implications For Future Behavioral Genetic Worksupporting
confidence: 68%
See 1 more Smart Citation
“…Second, because the findings did not appear to fully depend upon any one of the four SNPs-all contributed effects in the same direction and overlapped in their effect size confidence intervals in both samples-this work supports the future use of additive models, especially those located within a single neurobiological system that can then inform specific etiological pathways. Third, the findings support further investigation of HTR2A and its variant rs6314, because this interacted at a trend level with the cortisol awakening response to predict depression in recent work (Vrshek-Schallhorn et al, 2019b) and significantly predicted cortisol reactivity in these findings.…”
Section: Implications For Future Behavioral Genetic Worksupporting
confidence: 68%
“…The remaining three, rs6314, rs4570625, and rs6295, conformed to HWE (χ2s ≤ 1.699, ps ≥ .192). For consistency across the two samples, for the primary analyses, an MGPS was constructed from rs6314, rs4570625, rs6295, and 5HTTLPR, and secondary sensitivity analyses in Sample 1 probed whether the pattern of findings persisted when dropping 5HTTLPR or adding in HTR2C rs6318.1 The four variants available were used to compute the MGPS as described in a prior report (Vrshek-Schallhorn et al, 2015b), where all were coded for number of sensitivity alleles, 0-2 (designated as C for rs6314, G for rs4570625, and G for rs6295), with the exception of 5HTTLPR which was coded as S-carriers (0 = LL, 1 = SL or SS), following prior MGPS coding (Vrshek-Schallhorn et al, 2019b). Sensitivity alleles were summed (observed range 1-7, M = 4.42, SD = 1.14).…”
Section: Dna Collection Genotyping and Sensitivity Score Constructionmentioning
confidence: 99%
“…Factors that may help to unravel these associations in future research may include participant age and sex (see [ 32 ] for findings by sex) the duration of elevated symptoms (i.e., chronic versus recently emerged), and genetic risk. For example, using a 5-variant additive serotoninergic multilocus genetic profile score [ 50 ], found that a steeper CAR was associated with emergence of depression in young adults only among those with a higher genetic profile score. This line of research may be a promising path forward in understanding the role of diurnal cortisol in the biological sensitivity to context framework.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the past decade of research, the mechanism of interaction between genetic polymorphisms and environmental differences on psychopathology, especially depression, has received extensive attention (Hu et al, 2022;Zeng et al, 2023). Compared to a single polymorphism-environment design with lower explanatory power and higher false positive results (Januar et al, 2015;Starr et al, 2021;Starr and Huang, 2019), studies have found that genetic risk is cumulative, and polygenes have a greater cumulative effect size as well as stronger predictive power (Bulik-Sullivan et al, 2015;Hou et al, 2023;Vrshek-Schallhorn et al, 2019). In a study exploring the effect of five serotonin system polymorphisms and interpersonal stress on depression in 387 youth, Vrshek-Schallhorn et al (2015) found that the interaction of cumulative polygenic score and interpersonal stress affected depression after controlling for other stressful events.…”
Section: Effect Of Serotonergic Multilocus On Depressionmentioning
confidence: 99%